Book review of Jen Gilbert's (2014) Sexuality in School: The Limits of Education. Minneapolis, MN: University of Minnesota Press. - Farah Virani-Murji (Canadian Society for Studies in Education, 2018)
This text comprises of a book review of Sexuality in School: The Limits of Education by Jen Gilbert (2014). In her book, she encourages readers and educators to realize first, that sexuality is ordinary and part of the human condition, and second, that we cannot deny the reality of sexuality in our classrooms as our search for knowledge is inevitably charged with emotions such as love, aggression, and desire. Gilbert weaves together an insightful narrative of theory and practice, and offers a careful exploration of common debates of sexuality and adolescence, such as the idea of risk, the tendency to respond to challenges of identity with the assertion that the future will be better, and the responsibility that adults carry to inform the child of the world. Overall, Gilbert's book successfully responds and analyzes the misunderstandings of sexuality in our society today, and provides an alternative methodology to educators and policy makers of the concept of sexuality in education.